Inoculation of Cd-contaminated paddy soil with biochar-supported microbial cell composite: A novel approach to reducing cadmium accumulation in rice grains. (May 2020) - Liu, Yuling; Tie, Boqing; Peng, Ou; Luo, Haiyan; Li, Danyang; Liu, Shoutao; Lei, Ming; Wei, Xiangdong; Liu, Xiaoli; Du, Huihui
Abstract: Bioremediation of heavy metal-contaminated soil using metal-resistant microbes is a promising remediation technology. However, as exogenous bacteria sometimes struggle to survive and grow when introduced to new soils, it is important to develop appropriate carriers for microbial populations. In this study, we report a novel approach to remediating Cd-contaminated rice paddy soil using biochar-supported microbial cell composites (BMCs) produced from agricultural waste (cornstalks). Pot experiments showed that amendment with BMC was more efficient at reducing root and grain Cd content than pure bacteria, while improving soil Cd fractionation toward more stabilized and less labile forms. Bacteria in the BMC medium grew more readily with more abundant metabolites than those raised in free cells, probably because biochar provides shelter via porous structures (as confirmed by scanning electron microscopy) as well as additional nutrients. Overall, the improved long-term production of microbial biomass caused by BMC inoculation results in a higher remediation efficiency. Our results demonstrate the feasibility of using biochar as an appropriate carrier for metal-tolerant bacteria to remediate Cd-contaminated paddy fields. Highlights: Biochar-supported bacteria composite (BMC) is employed to remediate Cd contaminated soil. BMC reduces soil Cd availability and decreases Cd accumulation in rice grain. Microbial biomass is increased with BMC treatment in the long-term remediation.